A study of obesity, BMI, smoking and alcohol as risk factors for psoriatic arthritis. (28th February 2020) - Green, A.; Shaddick, G.; Charlton, R.; Snowball, J.; Nightingale, A.; Smith, C.; Tillett, W.; McHugh, N.; ,
Summary: Psoriatic Arthritis (PsA) is a progressive and often destructive joint disease affecting approximately 20% of people with psoriasis. PsA causes pain, swelling and joint stiffness and is accompanied by chronic skin disease and can lead to an impaired quality of life. It is helpful to understand the risk factors for developing PsA. The aim of this U.K. study was to examine the associations between obesity, changes in Body Mass Index (BMI), alcohol consumption, smoking status and the development of PsA in people with psoriasis. Data was collected from anonymised medical records and analysed. The authors found that increased risks of developing PsA were associated with an increased BMI, moderate drinking and ex‐smoking status. In addition, reducing BMI over a 10‐year period was associated with a reduction in the risk of developing PsA when compared to BMI remaining constant over the same period. In conclusion, while more studies are needed to investigate intentional weight loss on the risk of developing PsA, weight reduction amongst obese people with psoriasis may have the potential ability to prevent their excess risk of PsA while providing additional health benefits, including reduced cardiovascular and mortality risks. This is a summary of the study: Modifiable risk factors and the development of psoriatic arthritis in people with psoriasis Abstract : Linked Article: Green et al. Br J Dermatol 2020; 182 :714–720